Analysis and Modeling of Design Problems in the Context of Random Technological Changes - Knast, Paweł (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2025)
This paper presents a comprehensive methodology for modeling and analyzing complex design problems amidst random technological changes, developed through nearly three decades of international industrial research and practice. The evolution of design tools from traditional drawing boards in the 1980s to advanced 3D CAD systems today, combined with the author’s extensive global work experience, has informed this methodology. The proposed approach involves four critical phases: data collection, envisioning solutions, translating vision into computer models, and system implementation and refinement. Central to this methodology is the consideration of time as the main parameter for describing reality and random phenomena. By understanding time not only as a linear measure but as a multidimensional variable influencing all aspects of design and technological processes, the methodology addresses the inherent unpredictability and variability in modern engineering contexts. This method is designed to adapt to dynamic social, technical, economic, and legal conditions, ensuring robustness and flexibility. The paper concludes with a discussion on how this methodology can be seamlessly integrated into both workplace practices and educational curricula, emphasizing the importance of historical data and continuous improvement for future technological advancements.